Comparison of Fetal Outcome in Patients of Gestational Diabetes Treated with Met Formin and Insulin - Sajjad, Fatima; Usman, Shaheera; Choudhry, Abeera; Baloch, Shaheen Aslam; Aslam, Qurat Ul Ain; Shahid, Ghana (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare frequency of fetal outcome in patients of gestational diabetes being managed with Metformin and Insulin. Study Design: Comparative prospective Study. Place and Duration: Department of Obstetrics and Gynecology, Pak Emirates Military Hospital, Rawalpindi, from Apr to Dec 2016. Methodology: This study involved 286pregnant women aged between 18-40 years presenting after 24 weeks of gestation and diagnosed with gestational diabetes which were randomly allocated into two treatment groups. Patients in Group-A were treated with met for min while those in Group-B were treated with Insulin. Outcome variables were various fetal outcome measures which were noted and compared between the study groups. Results: The mean age of met for min group (32.71 ± 6.54 years) and Insulin groups (32.85 ± 6.10 years) was comparable. Mean APGAR score was similar between met for min and Insulin groups at 1 minute (7.56 ± 1.12 vs. 7.40 ± 1.13; p=0.229) and 5 minutes (8.34 ± 0.60 vs. 8.24 ± 0.67; p=0.231) after birth. The frequency of good APGAR (≥7) was significantly higher in met for min group at 1 minute (82.5% vs. 69.2%; p=0.009). Frequency of hyper-bilirubinemia (8.4% vs. 11.9%; p=0.327), respiratory distress syndrome (18.9% vs. 25.9%; p=0.156) and Neonatal Intensive Care Unit (NICU) admission (16.1% vs. 16.8%; p=0.873) showed no significant association with treatment method. Conclusion: The efficacy of met for min and Insulin was found to be comparable in the management of pregnancy with diabetes. Metformin was as safe as Insulin in treating gestational diabetes considering the fetal outcome.